Output characteristic and arc length control of pulsed gas metal arc welding process. (October 2017) - Wang, Qiang; Qi, Bojin; Cong, Baoqiang; Yang, Mingxuan
Abstract: A pulsed gas metal arc welding (P-GMAW) power source is produced with a stepped output characteristic. The steeped output characteristic control circuit is designed based on peak current-mode control and one cycle control methods An adaptive arc length control method is put forward and introduced based on a digital signal controller (DSC). Bead-on-plate experiments are carried out on mild steel to investigate the influences of output characteristics on the stability of P-GMAW process in an open-loop arc length control condition.Results show that stepped characteristic at background duration has the advantage of decreasing arc extinguishments and short-circuits phenomena, and the welding process is more stable without spatters than constant current or constant voltage characteristic. Welding with adaptive arc length control strategy, the dynamic behavior of arc working point and arc length is described, resulting in an identical arc length at the end of background time for each pulse period. One-drop-per-pulse transfer mode is obtained by carefully selecting pulse parameters with a droplet radius approximately equal to that of the electrode. Arc lengths are measured with different threshold voltages and background currents. The mathematical model of threshold voltage with respect to arc length and welding current is established through multiple linear regression analysis method. Welding with a step wire-feed speed and a step CTWD, the adaptive arc length control strategy shows strong disturbance resisting ability.